Phonological alterations of alveolar lateral sounds in Mewati: An analysis using Optimality Theory - Dedy Suhery; Mohd Hamid Raza; Zahratul Idami; Shafrida Wati; Cut Intan Meutia; Dessy Kurniasy; Rita Mahriza (Universitas Syiah Kuala, 2025)
This study examines the complex phonological shifts within the Mewati language, focusing on the transformation of the alveolar lateral sound between two vowels into an alveolar tap/flap. Using Optimality Theory (OT), our primary goal is to uncover the underlying process responsible for this phonological alteration. Fieldwork, in-depth interviews, and audio recordings were used to acquire extensive data. Together, these three data sources contribute to a comprehensive understanding of the phonological alteration under investigation. In summary, fieldwork provides the context, in-depth interviews offer insights into speakers perspectives, and audio recordings supply the raw phonetic data. The research field was Haryanas District Mewat, where we engaged a diverse group of fifty informants, including youth, adults, and the elderly. Mewati, a language native to Haryanas Mewat district exhibits a striking pattern. Our findings revealed that Mewati speakers relinquished the identity of the alveolar lateral sound if it did not occur between two adjacent vowels. These linguistic constraints serve as crucial determinants in evaluating potential output candidates, aligning them with the ranking features of input candidates in the framework of OT. The data collected from the heart of Mewat unequivocally confirms the presence of a phonological alteration process within the linguistic landscape of this region.